When calls the heart. Change of heart [videorecording (DVD)] - Fearnley, Neill; Wheeler, Anne. 1946-; Krakow, Erin; Lissing, Daniel, 1981-; Loughlin, Lori; Oke, Janette, 1935- (Frontier Productions : Millennium Entertainment, 2014)
"Elizabeth and Jack's relationship blossoms into romance in Change of Heart, the fifth installment of the When Calls the Heart series. Finally winning Elizabeth over, Jack is devastated to learn of his Constable reassignment. When Elizabeth s sister, Julie, arrives in Coal Valley with the new Constable, Jack reluctantly tells Elizabeth the news and must leave town. Julie, ever the curious one, stumbles upon a mysterious wounded man and rushes him to Abigail's for care, unknowingly putting herself, Abigail and Elizabeth in grave danger at the hands of the infamous Tolliver gang. Hearing of their distress, Jack rides back to Coal Valley to save the women in a desperate race against time."--Container.